Implementation of ADDIE in Multimedia to Improve Students' Understanding of Extrapolation - Sofhia Nabilah; Eka Fitrajaya Rahman; Asep Wahyudin (Universitas Pendidikan Indonesia, 2023)
Branching becomes one of the materials in basic programming subjects in vocational schools that have not been properly understood by the student. The observation results showed a problem in the learning process of the subject. The proposed solution to solve the identified problem is develop an interactive learning multimedia. Interactive multimedia helps solve problems by making the subject matter more interesting and easier to understand. This study aims to analyze the implementation of ADDIE model in the design and development of learning, improve student extrapolation understanding, and student response to multimedia. Interactive multimedia has been developed and rated